A Note on the Stability and Instability of Travelling Wave of Korteweg-de Vries Type: The Periodic Case - Quintero, José R (Revista de Ciencias, 2010)
In this paper we adapt the work of M. Grillakis, J. Shatah, and W. Strauss, or J. Bona, P. Souganidis and W. Strauss to the periodic case in spaces having the mean zero property in order to establish the orbital stability/instability of periodic travelling wave solutions of a generalized Korteweg-de Vries type equation.